PTU-066 Management of helicobacter pylori infection in patients with upper GI bleeding: compliance with guidelines. (June 2019) - Sullivan, Luke; Zakeri, Nekisa; Negus, Rupert; Morgan, Marsha Y
Abstract : Introduction: Acute upper gastrointestinal bleeding (AUGIB) is a common complication of peptic ulcer disease (PUD) defined as not only peptic ulceration but also erosive gastritis and duodenitis, Helicobacter pylori (H. pylori) infection is the major cause of PUD. NICE guidelines recommend that patients identified with PUD should be tested and treated for H pylori if infected. Post-eradication testing is mandated to confirm successful eradication. The aim of this study was to determine compliance with national guidelines for the management of H. pylori in those with PUD-associated AUGIB. Methods: Retrospective data were collected on all patients presenting to the Royal Free Hospital, London, with non-variceal AUGIB between 1 January and 31 December 2017. Prospective data were collected between 1 February and 1 April 2018. Compliance with guidelines was judged using predetermined criteria and classified as: poor (<67% compliance); moderate (67–75%); good (>75%); or excellent (>90%). Results: A total of 203 patients presented with non-variceal AUGIB during 2017, of whom 148 underwent endoscopy. Sixty-seven of those endoscoped met criteria for H. pylori testing but only 35 (52.2%) were investigated despite an absence of active bleeding or high-risk stigmata (compliance poor) (table 1 ). Of the 32 cases not tested, 22 exhibited overt ulceration at endoscopy, with the remaining cases demonstrating erosive changes. Four of the 55 non-endoscoped patients were tested for H pylori by other means. Overall, 15 (38.5%) of the 39 patients investigated tested positive for H pylori; 14 (93.3%) were prescribed eradication therapy (compliance excellent) while a further five patients were treated empirically. Of the 19 treated patients, only nine (47.4%) underwent post-eradication testing (compliance poor); all however tested negative. Prospective compliance rates in 36 patients exhibited similar poor compliance although samples were small (table 1 ). Conclusion: Approximately 50% of patients presenting with AUGIB with endoscopic features of PUD were not tested for H. pylori. Almost 40% of those who were tested were infected. Post-eradication investigation rates were particularly low. No clear explanation for this level of non-compliance with guidelines is apparent but enforcement is clearly warranted.